Argon Plasma Coagulation (APC) for the Treatment of Excessive Dynamic Airway Collapse (EDAC): An Animal Pilot Study. Issue 3 (July 2021) - Kheir, Fayez; Ospina-Delgado, Daniel; Beattie, Jason; Singh, Rani; Vidal, Barbara; VanderLaan, Paul A.; Parikh, Mihir; Chee, Alex; Gangadharan, Sidhu P.; Wilson, Jennifer; Majid, Adnan
Abstract : Background: Surgical stabilization of the airway through tracheobronchoplasty (TBP) is the current treatment modality for patients with severe symptomatic excessive dynamic airway collapse. However, TBP is associated with increased morbidity and mortality. Bronchoscopic treatment of the posterior membrane using argon plasma coagulation (APC) may be a safer alternative to TBP in highly selected patients. This study aimed to evaluate the effect of APC in the tracheobronchial tree of a sheep animal model. Patients and Methods: Two adult sheep were used for this study. Under flexible bronchoscopy, the posterior tracheal membrane was treated with precise APC using different power settings. Chest computed tomography was done at 2 days and bronchoscopy was performed at 30 days following initial procedure, before euthanasia. The airways were assessed for the presence of treatment-related histopathologic changes along with expression of genes associated with fibrosis. Results: There was no perioperative or postoperative morbidity or mortality. Chest computed tomography showed no signs of pneumomediastinum or pneumothorax. Flexible bronchoscopy showed adequate tracheobronchial tissue healing process, independent of the power settings used. Histologic changes demonstrated an increased extent of fibroblastic collagen deposition in the treated posterior membrane when higher power settings were used. In a similar manner, APC treatment managed to activate fibrosis-associated gene transcription factors, with higher settings achieving a higher level of expression. Conclusion: APC at high-power settings achieved higher levels of fibroblast collagen deposition at the posterior membrane and higher expression of fibrosis-associated gene transcription factors, when compared with lower settings.